Psychiatric Discourse and Colonial Ideology in British Africa - Santos, Gisele Silva [UNESP] (Univ Estadual Londrina, 2016)
Psychiatric studies produced by Europeans during colonial period on African mental disorders contribute to a reflection over human sciences' normative and paradigms. Considering Foucault's statement that madness in modern western society can be defined as a discourse constitutive of power relations, the article investigates how colonial states exercised power through psychiatric theories and its discourses. Psychiatric studies in colonial Africa give the means to an interpretation of what was considered normal and pathological in that context and provide significant evidence about the ambiguity in the conclusions reached by those physicians and researchers. The essay explores a set of psychiatric writings produced during 1920-1960, a period marked by the triggering of nationalist and pro-independence movements. The main goal here is to shed light on the relationship between the Western medicine and colonial authority and demonstrate how this alliance promoted the control of colonial powers on the African population. It was concluded that during the process of decolonization in Africa, when was the ruling force constantly in disagreement with the native black population, the psychiatric knowledge played the role of legitimizing element of the civilizing mission.
Keywords: British Colonial Africa; Ethnopsichiatry; Scientific discourse; Nationalist uprisings; Colonial ideology